Phytochemical Study of the Plant Centaurea bruguieriana (DC.) Hand.-Mazz. subsp. belangeriana (DC.) Bornm. of the Family Asteraceae - Kyriakos Michail Dimitriadis; Olga Tsiftsoglou; Dimitra Hadjipavlou-Litina; Mohammad Arfan; Diamanto Lazari (Separations)
The aim of this study is to isolate and identify the secondary metabolites of the aerial part of the plant Centaurea bruguieriana (DC.) Hand. -Mazz. subsp. belangeriana (DC.) Bornm. (Centaurea phyllocephala) (Asteraceae), and to study the biological activities of the extracts and isolated compounds with in vitro tests. With the use of chromatography and spectroscopy we identified three elemanolides: 8α-O-(3,4-dihydroxy-2-methylenebutanoyloxy) dehydromelitensine (1), 8α-O-(3-hydroxy-4-acetoxy-2-methylene-butanoyloxy) dehydromelitensine (2) and methyl 6α,8α,15-trihydroxyelema-1,3,11(13)-trien-12-oate (3); two germacranolides: cnicin (4) and 4′-O-acetylcnicin (5); one eudesmanolide: malacitanolide (6); five flavonoids: cirsilineol (7), eupatorine (8), 5-hydroxy, 6,7,3′,4′-tetramethoxy-flavone (9), 3,4′,5,7-tetrahydroxy-6-methoxyflavone 3-O-β-D-glucopyranoside (10) and astragalin (11); and also p-OH-benzoic acid (12) and 3-hydroxy-2-methyl-butyrolactone (13). All the isolated compounds were evaluated in silico with the use of molinspiration, while the crude extract, the organic phase B and compounds 2, 4, 5 and 6 were tested as antioxidants and anti-inflammatories for the inhibition of lipid hyperoxide and the inhibition of lipoxygenase.